EFEKTIVITAS KINERJA KARYAWAN DALAM PELAYANAN JASA PEMBERIAN KREDIT GADAI PADA KANTOR PEGADAIAN UNIT PELAYANANAN CABANG PANGKAJENE KABUPATEN SIDENRENG RAPPANG - Kharisna Kharisna; Monalisa Ibrahim; Kamaruddin Sellang (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
This This study aims to determine the effectiveness of employee performance in the service of providing pawn loans at the Pangkajene Branch Service Unit Pangkajene Branch, Sidenreng Rappang Regency. The population and sample in this study were customers who used pawn credit services as many as 97 people and used saturated sampling. This study uses a quantitative approach. Data collection techniques by observation, interviews, questionnaires and documentation. The collected data were then analyzed using frequencyandpercentagetables. The results showed that the effectiveness of employee performance in the service of providing pawn loans at the Pangkajene Branch Service Unit of the Pangkajene Branch Office of Sidenreng Rappang Regency was good with an average percentage of 85.25%. While the factors that affect the effectiveness of services providing pawn credit services at the Pangkajene Branch Service Unit of Sidenreng Rappang are good with an average percentage of 80.08% seen from service procedures, settlement time, service fees, service products, facilities and infrastructure and officer competence.